Network-based system for acoustic mapping of urban areas - Jan Kazmierczak; Adam Lipowczan; Piotr Sasiedzki (European Regional Science Association (ERSA), 2002)
The paper presents both a general idea and basic assumptions of the research project, which was started a year ago at Technical University of Silesia, Poland and primarily has been focused on the Region of Upper Silesia. At present, the project is prepared to cover other regions of the country. In particular, the research area of this project contains the problems of preparing and utilizing the acoustical maps of towns that ought to be prepared in accordance with the EC directive com468 (2000). The main two assumptions of the project are as follows: 1) the maps will be prepared by means of advanced computer-based tools of the GIS and GPS classes, 2) both the procedures of developing and utilizing the acoustical maps will be executed in the form of group-work using the PIONIER (Polish Optical Internet) NREN and Intranet tools for online collaboration and audiovisual communication with utilization of resources available at network and HPC centers across the country. It is assumed that the system as primarily being developed for the needs of local scale mapping thanks to the network approach will be adaptable also for larger (regional) scale enterprises. The paper discusses briefly the current state of research in the mentioned field in Poland. The second part of the paper presents the timetable of further activities with a specification of expected results. Apart from the 'technical' problems of acoustic mapping of urban areas, the paper also deals with some 'non-technical' aspects of this field of activity. The final part of the paper introduces some perspectives of dissemination of results of the reported research in the process of European enlargement.
Keywords: 330